Service-Learning and Teacher Resilience: A Bidirectional Engine for Healing School Coexistence - Martínez Ortega, Jesús Francis (2025)
In the everyday fabric of Mexican public secondary schools, the emotional fragility of those learning to teach intertwines—almost unnoticed—with the convivial frictions that cut through adolescent hallways. Probing the extent to which these threads knot together—or unravel—when brought into contact with a service-learning experience forms the backdrop of the present work. This study assessed the effect of an emotional-intelligence-based Service-Learning (SL) programme on the affectivewell-being of 27 pre-service teachers and the classroom climate of 97 seventh-grade students at a public secondary school in Mérida, Mexico. A one-group quasiexperimental design with a retrospective pretest and immediate post-test wasapplied. After eight intervention sessions, pre-service teachers completed semistructured online interviews, and students answered mixed questionnaires. Postthen- pre comparisons revealed significant anxiety reductions (Md 4 → 2; p < .001)and substantial gains in teaching self-efficacy (Md 2 → 4; p < .001). Students reported a 46 % decrease in peer conflicts and a 31 % increase in collaborative willingness. Thematic analysis showed that strengthened teacher resilience—rootedin bodily self-awareness—mirrored students’ improved impulse regulation and empathetic behaviour, supporting the SL bidirectionality hypothesis: self-care enables care for others. Embedding SL-emotional modules in initial teachereducation appears to enhance teacher resilience and foster healthier school climates; sustained mentoring is nevertheless required to prevent trainee fatigue and to address out-of-school stressors.